Semiotic Analysis of Medical Diagnosis - Silveira, Lauro Frederico Barbosa da (2013)
Medical diagnosis considered under a semiotic standpoint consists in complex dialogic process between physician and the patient. Both play essential roles in order do be settled the suggestive diagnostic hypotheses. By mean of a diagram wherein the phenomenological categories proposed by Peirce play the role of as vectors characterizing the several activities and experiences composing the process. The full process is a very long one, although it can be abbreviated due to the urgency in determining the therapeutic conduct or by the precipitation, at least, of one of the participant. The sequence of the activities can also change in their direction depending of the course of the dialogue, as in all dynamic and non deterministic process.